The influence of light physical activity on scale of pain in elderly with knee osteoarthritis - Prasenah Subramaniam; Nyoman Astika; Ketut Mariadi (Intisari Sains Medis, 2019)
Background: Osteoarthritis (OA) is a collection of mechanical variations of joint thinning, including the articular ligament and the subchondral bone.Aim: This study aims to find out how some light physical activity correlates with the pain scale among elderly with knee osteoarthritis and also to find out whether light physical activity in the elderly helps reduce pain in knee osteoarthritis.Method: This research is a descriptive cross sectional study. The sample in this study was elderly people aged 50 years and above with a total of 70 samples were selected using multistage random sampling technique located in Badung Market, Kumbasari Market, and Renon Field. Data were obtained by interviewing respondents who previously provided informed consent using structured questionnaires. The degree of pain caused by osteoarthritis was measured using The Western Ontario and McMaster University Osteoarthritis Index (WOMAC) and the total score.Results: Distribution of sex within samples found that women (54.3%) and men (45.7%). Researchers found that the mean age of respondents was 61.2 (SD + 3.75) years. The total number of respondents who have exercise habits is 52.9%. The average WOMAC score was 23 (SD +2,319) with a minimum score of 18 and a maximum of 27. Respondents with WOMAC score <23 were 52.9% whereas respondents with WOMAC score> 23 were 47.1%. Cross-tabulation results showed 97.3% of respondents with a WOMAC score <23 had exercise habits.Conclusion: The exercise habits of the elderly with knee osteoarthritis can reduce pain when measured using a 0-4 scale and the WOMAC pain scale.